[18F]AV‐1451 tau‐PET and primary progressive aphasia. Issue 3 (13th March 2018) - Josephs, Keith A.; Martin, Peter R.; Botha, Hugo; Schwarz, Christopher G.; Duffy, Joseph R.; Clark, Heather M.; Machulda, Mary M.; Graff‐Radford, Jonathan; Weigand, Stephen D.; Senjem, Matthew L.; Utianski, Rene L.; Drubach, Daniel A.; et al.
Abstract : Objectives: To assess [ 18 F]AV‐1451 tau‐PET (positron emission tomography) uptake patterns across the primary progressive aphasia (PPA) variants (logopenic, semantic, and agrammatic), examine regional uptake patterns of [ 18 F]AV‐1451 independent of clinical diagnosis, and compare the diagnostic utility of [ 18 F]AV‐1451, [ 18 F]‐fluorodeoxygluclose (FDG)‐PET and MRI (magnetic resonance imaging) to differentiate the PPA variants. Methods: We performed statistical parametric mapping of [ 18 F]AV‐1451 across 40 PPA patients (logopenic‐PPA = 14, semantic‐PPA = 13, and agrammatic‐PPA = 13) compared to 80 cognitively normal, Pittsburgh compound B–negative controls, age and gender matched 2:1. Principal component analysis of regional [ 18 F]AV‐1451 tau‐PET standard uptake value ratio was performed to understand underlying patterns of [ 18 F]AV‐1451 uptake independent of clinical diagnosis. Penalized multinomial regression analyses were utilized to assess diagnostic utility. Results: Logopenic‐PPA showed striking uptake throughout neocortex, particularly temporoparietal, compared to controls, semantic‐PPA, and agrammatic‐PPA. Semantic‐PPA and agrammatic‐PPA showed milder patterns of focal [ 18 F]AV‐1451 uptake. Semantic‐PPA showed elevated uptake (left>right) in anteromedial temporal lobes, compared to controls and agrammatic‐PPA. Agrammatic‐PPA showed elevated uptake (left>right) throughout prefrontal white matter and in subcortical gray matter structures, compared to controls and semantic‐PPA. The principal component analysis of regional [ 18 F]AV‐1451 indicated two primary dimensions, a severity dimension that distinguished logopenic‐PPA from agrammatic‐PPA and semantic‐PPA, and a frontal versus temporal contrast that distinguishes agrammatic‐PPA and semantic‐PPA cases. Diagnostic utility of [ 18 F]AV‐1451was superior to MRI and at least equal to FDG‐PET. Interpretation: [ 18 F]AV‐1451binding characteristics differ across the PPA variants and were excellent at distinguishing between the variants. [ 18 F]AV‐1451binding characteristics were as good or better than other brain imaging modalities utilized in clinical practice, suggesting that [ 18 F]AV‐1451 may have clinical diagnostic utility in PPA. Ann Neurol 2018 Ann Neurol 2018;83:599–611